Crohn's Disease Imaging: A Review. (27th February 2012) - Gatta, Gianluca; Di Grezia, Graziella; Di Mizio, Veronica; Landolfi, Cinzia; Mansi, Luigi; De Sio, Ilario; Rotondo, Antonio; Grassi, Roberto
Abstract : Crohn's disease is a chronic granulomatous inflammatory disease of the gastrointestinal tract, which can involve almost any segment from the mouth to the anus. Typically, Crohn's lesions attain segmental and asynchronous distribution with varying levels of seriousness, although the sites most frequently involved are the terminal ileum and the proximal colon. A single gold standard for the diagnosis of CD is not available and the diagnosis of CD is confirmed by clinical evaluation and a combination of endoscopic, histological, radiological, and/or biochemical investigations. In recent years, many studies have been performed to investigate the diagnostic potential of less invasive and more patient-friendly imaging modalities in the evaluation of Crohn's disease including conventional enteroclysis, ultrasonography, color-power Doppler, contrast-enhanced ultrasonography, multidetector CT enteroclysis, MRI enteroclysis, and 99mTc-HMPAO-labeled leukocyte scintigraphy. The potential diagnostic role of each imaging modality has to be considered in different clinical degrees of the disease, because there is no single imaging technique that allows a correct diagnosis and may be performed with similar results in every institution. The aim of this paper is to point out the advantages and limitations of the various imaging techniques in patients with suspected or proven Crohn's disease.